A bitter feast [compact disc, unabridged] - Crombie, Deborah (Crombie, Deborah. Duncan Kincaid & Gemma James., 2019)
Scotland Yard Detective Superintendent Duncan Kincaid and his wife, Detective Inspector Gemma James, have been invited for a relaxing weekend in the tranquil Cotswolds that contains timeless villages that retain the spirit of old England. Duncan, Gemma, and their children are guests at Beck House, the country estate belonging to the family of Melody Talbot, Gemma's trusted detective sergeant. A centerpiece of this glorious fall getaway is a posh charity luncheon catered by up-and-coming chef Viv Holland. Attended by several dozen of the area's well-to-do, as well as national food bloggers and restaurant critics, the event could make Viv a star. But a tragic car accident followed by a series of mysterious deaths could ruin her ascent. Each piece of information that surfaces make it clear that the killer had a connection with Viv's pub, and perhaps with Beck House itself.